(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Renal failure or dysfunction: A disease occurs by a severe weakness in one kidney or both, they lose ability to do their functions effectively, resulting in the body’s inability to remove waste and fluids, Leading to a significant changes in chemistry of blood and body fluid. The study occurred in Karbala province where study samples were collected, which included (124). Samples divided in (64) patients and (60) control, patients had another division according to sex (44) male and (20) female. Immunologic parameters include (kidney injury molecules (KIM-1), pro-inflammatory TNF-?, IgG antibodies) Elabscience Kit, concentration in serum was massacred by (ELISA) Technique and hematologic test measured automatically by (Humlate plus-1 Device). The results showed increase in kidney injury in age groups beyond the age of 40 years. A significantly higher incidence of disease among males more than females. Results show significant statically variations in serum levels: 1- kidney injury molecules (KIM-1) levels was increased in serum in patients significantly compare with control. 2- (TNF-?) levels was increased in patients than control. 3- IgG levels decreased in patients than control. Another routine tests occurs to patients to know the effects of disease on blood variations, the test was included CBC count the results show CBC tests: (WBC, MHC, MCHC, RDWS, RDWC, PLT, PCT, PDWS, PDWC, P-LCC and P-LCR) have no significant differentials while CBC tests: (LYM., MON., GRA., RBC., HGB., HCT., MCV, MPV) which decrease in patient compare with control significantly. Increase kidney injury and inflammatory in serum patients with disease, by measured some parameters levels in sera as indicators for disease progression and decrease in some antibodies such as IgG concentration of in sera, as well as the hematologic tests referrer to disease may associated with anemia.